Risk Factors of Suicide and Para Suicide in Rural Bangladesh - Reza, AM Selim; Feroz, A H M; Islam, SM Nurul; Karim, Md. Nazmul; Rabbani, Md. Golam; Shah Alam, Md.; Rahman, M Mujibur; Rahman, Md. Ridwanur; Ahmed, Helal Uddin; Bhowmik, Avra Das; Khan, Muhammad Zillur Rahman; Sarkar, Mekhala; et al. (Journal of Medicine, 2014)
Background: Suicide is a public health problem too often neglected by researchers, health policy makers and the medical profession. In the year 2000, approximately one million people died of suicide which represents a global mortality rate of 16 per 100,000. According to WHO estimates for the year 2020 and based on current trends approximately 1.53 million people will die from suicide and 10-20 times more people will attempt suicide worldwide. This represents on average 1 death per 20 seconds and 1 attempt every 1-2 seconds. No nationwide survey on suicidal risk factors has yet been conducted in Bangladesh. Reports from police records, Media, court, hospitals and the focused study on selected population indicate that suicide is a public health problem in Bangladesh. The aim of this study was to unearth the potential risk factors of suicide or suicidal attempts and to assess psychiatric illness, non psychiatric co-morbidity, individuals behavioral and physical factor, familial risk factors and socio-demographic risk factors of suicide and its attempts. Study Design and Setting: A case control study was carried out by members of the Department of Medicine, Shaheed Suhrawardi Medical College and Hospital at Mominpur,Haowlee and Jibonnagar unions under three Upazilla of district Chuadanga,. Statistical analyses were performed using SPSS 16. Results: A total 230 subjects (113 cases and 117 controls) were interviewed. Mean age among cases was 29.6±12.8 years and controls were 29.7±12.9 years.Majority of the participants, 65.5% of cases and 63.2% of controls were aged between 20-39 years. Among cases 38.9% were male and among the controls 42.7% were male.Among cases 30.1% and among controls 27.4% had less than 4 family members. More than half of the participants, among cases (58.4%) and among controls (55.6%) had between 4- 6 members in the family. Economic status was also similar in two groups.Problem of love affair (OR 5.2), Personal problem (OR 11.9), Feeling of economic hardship (OR 2.4) appeared to have statistically significant association with suicidal attempt. Problem with relatives (OR 3.8), death of near relative (OR 0.9) and poor academic performance (OR 1.6) didnt appear to have any association with risk of suicidal attempt. History of chronic disease (OR 2.9) showed statistically significant association but long term physical disability (OR 4.4) and physical problems didnt appear to have any significant association with suicidal attempt. History of suicidal attempt by any relative (OR 4.2) and previous attempt to suicide (OR 7.4) appeared as highly significant factor for suicide. Not being reared by biological parents (OR 3.2), marital disharmony (OR 4.0), Conflict within the family (OR 6.9) appeared to be strongly associated with suicidal attempts. Suicidal attempts of participants were significantly associated with sleeping disturbance (OR 2.3), uncertainty about future (7.2), impulsivity (OR 13.8), and history of criminal behavior (OR 2.1). Conclusion: Case control study on the risk factors of suicide in rural area of South-West Bangladesh revealed that the married female especially the younger age from unitary family of low income group are more vulnerable to commit suicide or parasuicide. Several emotional factors, presence of chronic diseases, familial suicidal predisposition, individual factor and mental state, premorbid persionality and psychiatric syndrome appeared to have significant association with suicidal attempts. DOI: http://dx.doi.org/10.3329/jom.v14i2.19653 J Medicine 2013, 14(2): 123-129